Diagnostic performance of dual-staining cytology for cervical cancer screening: A systematic literature review. (March 2017) - Tjalma, Wiebren A.A.
Abstract: Cervical cancer screening saves lives. Secondary prevention in cervical cancer screening relies on the results of primary cytology and/or HPV testing. However, primary screening with cytology has a low sensitivity, and HPV screening has a low specificity. This means that either cancers are missed, or women are over-treated. To improve performance outcomes, the concept of dual-stain cytology (CINtec ® PLUS Cytology test) has been introduced. In this approach, additional staining with p16/Ki-67 is performed in cases where cytology results are abnormal (LSIL or ASCUS) and/or HPV-positive. Another way to describe this approach might be "diagnostic" cytology. In order to assess the value of this "diagnostic cytology", a systematic literature review was conducted of dual-stain cytology performance across multiple studies until May 2016. In a Belgian screening population (women age 25–65 years), dual-stain cytology was significantly more sensitive (66%) and slightly less specific (−1.0%) than cytology. In the population referred to colposcopy or with abnormal cytology (ASCUS, LSIL), dual-staining showed a significantly higher increase in specificity, and a slightly lower sensitivity than HPV testing. Specificity gains resulted in fewer false positives and an increase in the number of correct referrals to colposcopy. Dual-staining with p16/Ki-67 cytology is an attractive biomarker approach for triage in cervical cancer screening.